Structure of human rhinovirus complexed with Fab fragments from a neutralizing antibody. - Smith, T J (1993)
We have determined the structure of a human rhinovirus (HRV)-Fab complex by using cryoelectron microscopy and image reconstruction techniques. This is the first view of an intact human virus complexed with a monoclonal Fab (Fab17-IA) for which both atomic structures are known. The surface area on HRV type 14 (HRV14) in contact with Fab17-IA was approximately 500 A2 (5 nm2), which is much larger than the area that constitutes the NIm-IA epitope (on viral protein VP1) defined by natural escape mutants. From modeling studies and electrostatic potential calculations, charged residues outside the neutralizing immunogenic site IA (NIm-IA) were also predicted to be involved in antibody recognition. These predictions were confirmed by site-specific mutations and analysis of the Fab17-IA-HRV14 complex, along with knowledge of the crystallographic structures of HRV14 and Fab17-IA. The bound Fab17-IA reaches across a surface depression (the canyon) and meets a related Fab at the nearest icosahedral twofold axis. By adjusting the elbow angles of the bound Fab fragments from 162 degrees to 198 degrees, an intact antibody molecule can be easily modeled. This, along with aggregation and binding stoichiometry results, supports the earlier proposal that this antibody binds bivalently to the surface of HRV14 across icosahedral twofold axes. One prediction of this model, that the intact canyon-spanning immunoglobulin G molecule would block attachment of the virus to HeLa cells, was confirmed experimentally.